2019
DOI: 10.3390/met9121341
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Contact Heating of Aluminum Alloy Sheets in Hot Stamping Process

Abstract: Application of the hot stamping process on heat-treatable aluminum alloys effectively solves the problems of large springback and poor ductility during forming at room temperature, which expands the range of applications of aluminum alloys in the transportation industry. Sheet heating plays an important role in the hot stamping process, and increasing the heating rate can improve the hot stamping efficiency to some extent. In this paper, the feasibility of applying contact heating techniques with higher heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, they also found that the temperature uniformity was inadequate, and proposed that the configuration of the flame nozzles be arranged reasonably to enhance the temperature distribution across the sheet. Our research indicates that using the contact heating process on a 7075 sheet with a thickness of 2 mm, can achieve solid solution temperature (480 o C) within 15 to 20 seconds [7].…”
Section: Introductionmentioning
confidence: 79%
“…However, they also found that the temperature uniformity was inadequate, and proposed that the configuration of the flame nozzles be arranged reasonably to enhance the temperature distribution across the sheet. Our research indicates that using the contact heating process on a 7075 sheet with a thickness of 2 mm, can achieve solid solution temperature (480 o C) within 15 to 20 seconds [7].…”
Section: Introductionmentioning
confidence: 79%
“…It was developed a steady-state thermal FEM analysis considering the convection phenomena. Approximate convection coefficient values for aluminum alloys were confronted with those presented by Geng et al [ 23 ]. It has conducted the analyses on ABS simulating the heat transfer for the cool environment, which starts from around −10 ° C and records about 13 °C on the top side of the cover plate ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…18. The result showed that the heating rate reached 28.7 °C/s and the heating time to a solution treatment temperature of aluminum alloy could be reduced from around 8 min to 15-20 s in comparison with furnace heating [64]. Contact heating is also one good solution for partial heating by controlling the contact surface.…”
Section: Contact Heatingmentioning
confidence: 99%
“…17 Sequence of bending processes with local infrared heating [63] Fig. 18 The schematic of a device and b contact heating [64] Fig. 19 Cylindrical deep drawing by partial contact heating and whole furnace heating [65] cooling rates could be one of the significant challenges for its application.…”
Section: Contact Heatingmentioning
confidence: 99%